2013
DOI: 10.1021/es400559a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Magnetic Recoverable Nanosize Cu–Fe2O3/Fe Photocatalysts

Abstract: Iron based catalysts generally have the advantage of the easily operated magnetically recovery from application sites. In the present work, paramagnetic iron and copper core-shell nanoparticles having the iron fractions (X(Fe) = Fe/(Cu+Fe)) of 0.33-1.0 were prepared and characterized by in situ synchrotron X-ray absorption and scattering spectroscopy. During the temperature-programmed carbonization (TPC) of Cu(2+)- and Fe(3+)-β-cyclodextrin (CD) complexes, a rapid reduction of Cu(II) occurs at about 453 K toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 40 publications
(59 reference statements)
0
16
0
1
Order By: Relevance
“…The high photo-Fenton activity and high stability of the as-synthesized samples may be attributed to the synergistic coupling effects in these samples: (1) the unique morphologies of 0D QDs (ca. 36 To elucidate the mechanism involved in the photo-Fenton degradation of organic contaminant, trapping experiments for both • OH and O 2 •− have been conducted in this work to determine the specific reactive species that played a major Fig. 31,37 (2) 2D graphene sheets could be regarded as ideal conductive substrates, which may improve the electron transport.…”
Section: Resultsmentioning
confidence: 99%
“…The high photo-Fenton activity and high stability of the as-synthesized samples may be attributed to the synergistic coupling effects in these samples: (1) the unique morphologies of 0D QDs (ca. 36 To elucidate the mechanism involved in the photo-Fenton degradation of organic contaminant, trapping experiments for both • OH and O 2 •− have been conducted in this work to determine the specific reactive species that played a major Fig. 31,37 (2) 2D graphene sheets could be regarded as ideal conductive substrates, which may improve the electron transport.…”
Section: Resultsmentioning
confidence: 99%
“…810 The use of Cu as a dopant, alone or in combination with other metals, in iron oxide nanoparticles, is limited, compared, for example, to its use as a dopant in ZnO nanoparticles. Cu doping effect has been studied in catalysis, 11 sensor performance, 12,13 and in the magnetic properties of the nanomaterial. 1416 The use of Cu as a dopant for molecular imaging is limited, with one example, in combination with Co, using nanorods for MRI 17 and one example where the 64 Cu radioisotope is used for positron emission tomography.…”
Section: Introductionmentioning
confidence: 99%
“…However, carcinogenic by-products such as halogenated hydrocarbons in those chemical oxidation processes may be formed (Lata & Samadder, 2016). Molecular-scale data such as coordination number (CN), bond distance and oxidation state of select elements in a complicated matrix can be determined by X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine-structure (EXAFS) spectroscopy (Kang & Wang, 2013;Huang et al, 2003;Lin & Wang, 2000;Liu & Wang, 2004). By EXAFS, in the previous studies, we found that copper oxide clusters are involved in catalytic decomposition of NO and oxidization of chlorophenols (in supercritical water) .…”
Section: Introductionmentioning
confidence: 99%